The Cross‐Section of Realized Stock Returns: The Pre‐COMPUSTAT Evidence - DAVIS, JAMES L. (Journal of Finance, 1994)
ABSTRACT Using a database that is free of survivorship bias, this article finds that book‐to‐market equity, earnings yield, and cash flow yield have significant explanatory power with respect to the cross‐section of realized stock returns during the period from July 1940 through June 1963. There is a strong January seasonal in the explanatory power of these variables, even though small stocks are, by construction, excluded from the sample.